Da utopia a realidade: oportunidades e desafios do cooperativismo solidário no Brasil na perspectiva dos associados - Zanco, Alcidir Mazutti (2020)
The Thesis - From utopia to reality: Opportunities and challenges of Solidary Cooperativism in Brazil from the perspective of Associates, aims to analyze the capacity of this Cooperativism, in promoting the participation of Associates from the Actor Oriented Perspective (POA), starting from the statement that the consolidation of the Brazilian Solidarity Cooperativism is defined by the participation format of the Associates and the consistency of its organization and development proposal. The study is descriptive of a qualitative and quantitative nature with a longitudinal cut for the years 2005 to 2020. The data survey was carried out in partnership with the National Union of Cooperatives of Family Agriculture and Solidarity Economy (UNICAFES), with the application of questionnaires in three phases: In the first phase, information was collected on the profile of Solidarity Cooperatives with the participation of 372 Cooperatives; In the second phase, information on the ability of Cooperatives to promote the participation of Associates, with the participation of 1.030 people from all regions and states in Brazil; In the third phase, on the socioeconomic results achieved by these Cooperatives in the years 2017-2020. To confirm the information collected by these questionnaires, interviews were conducted with Administrative Advisers of the Cooperatives who obtained the best results in all states of Brazil. To analyze these data, a theoretical basis is used on Modern Cooperativism, specificities of the Agricultural Branch and Solidary Cooperativism from the perspective of the Associates. The Study was developed in a context of organizational adversity, in which the Cooperatives seek to define and optimize indicators that promote greater participation of the Associates, with a view to consolidating their differentials and structuring characteristics. Faced with this problem, the Survey mapped and analyzed the Associates' perspective and vision. The results show that this Cooperativism has as its main sustainability indicator, the active participation of Associates and its proposal for productive development, affirming the need to qualify these social, cultural and economic differentials with recommendations that suggest innovations in the organizational management of Cooperatives.